Sensitivity of methods for estimating reference evapotranspiration - Dobos, Attila; Rácz, Csaba; Nagy, János (Acta Agraria Debreceniensis, 2014)
The knowledge of the evapotranspiration of natural ecosystems and plant populations is of fundamental importance in several branches of science, research topics and practical uses. Nevertheless, the harmonization of the large number of methods and the changing user needs often causes problems. Sensitivity analysis of 10 ET0 estimation models and model variants was performed. Magnitude of the obtained outputs and the changes triggered by each atmospheric parameter were evaluated. The objective of the analyses was to get to know the sensitivity of the different models and to select the most accurate and the most suitable ones for adaptation to local circumstances. Therefore, it becomes possible to achieve as high accuracy as possible in applications which need ET0 estimation.